Krisis Pengetahuan Lokal: Terputusnya Rantai Pendidikan Pertanian Padi di desa jambuwer. - Haryana, Desvandy Saputra; Mahardika, Putri Mayo (Studi Budaya Nusantara, 2024)
The young generation’s preference for rice farming in Galagarum Hamlet, Jambuwer Village, Malang Regencyseems to have undergone significant changes. This research examines the cessation of rice farming education thatpreviously has been passed down from generation to generation, caused by the loss interest of the young generation in agriculture, and the cessation of the local knowledge education program, named ‘Penyuluhan Pelatihan Lapangan (PPL)’ that specialized in rice farming. This research used qualitative methods and an Ethnography approach, involving in-depth interview and participant observation for data collection. Using Anthony Giddens' theory of structuralization, this research proves that agents and social structures are interrelated and can cause social change. The result of this research shows that the disconnection of the farmer generation is caused by the negative stigma that is attached to rice farmers, economic opportunities and many jobs outside agriculture that seems more attractive for the younger generation, and the absence of non-formal education encouragement such as PPL. Youth generation in Galaharum hamlet, Jambuwer village tend to choose to continue their education in Sekolah Menengah Kejuruan (SMK) which offers direct access to jobs in the industrial and mining sectors. As a result, many farmers in Jambuwer Village are forced to choose to hire farm laborers to manage their land, or in some cases, sell it. This research proves that the development of non-formal education, such as rice farming education, is very useful to reengage the young generation's interest in the agrarian sector and maintain the agricultural heritage.